Aplicação de ácido abscísico e etefom na qualidade de uvas Merlot para vinificação - Susin, Eliane (My University, 2021)
The Merlot grape is a cultivar of French origin, from the Bordeaux Region. In Serra Gaúcha, it is the second variety of paint with the largest area of vineyard implanted, with 472 ha. Currently, viticulture has been using plant regulators as an alternative to promote an increase in the quality of musts. Abscisic acid and ethephon are alternatives used to supply the lack of color of the consequences caused by climatic adversity in regions with low thermal amplitude and rainy or cloudy periods in the maturation phase. These plant regulators promote the accumulation of pigments that give color to the berries. In order to verify the effect of the application of abscisic acid (ABA) and ethephon on the final quality of wines from cv. Merlot, the present experiment was obtained in two commercial vineyards, in the municipalities of Campestre da Serra, with geographical coordinates of 28 ° 40 'S and 51 ° 06' W and Antônio Prado with geographical coordinates of 28 ° 53 'S 51 ° 20' W, both occurring in the Serra Gaúcha, Southern Brazil. The treatments were mandatory in two stages: color change (V) and 15 days before harvest (15 DAC). As applied doses were: T0 (control); T1 (etefom 200 mg?L-1 - V); T2 (etefom (200 mg?L-1 - 15 DAC); T3 (etefom 200 mg?L-1 - V + S-ABA 600 mg?L-1 - 15 DAC); T4 (S-ABA 600 mg?L-1 - V); T5 (SABA 600 mg?L-1 - 15 DAC); T6 (S-ABA 300 mg?L-1- V + S-ABA 300 mg?L-1 - 15 DAC); T7 (S-ABA 600 mg?L-1 V + etefom 200 mg?L-1 - 15 DAC) The following parameters were determined for grapes: mass and diameter of berries, content of soluble solids, pH of must, content of phenolic compounds and anthocyanins. For wines, the content of alcohol (ethanol), color, density, total acidity, color index, shade and residual sugar content were evaluated. The results induced by the location of the vineyards and climate do not reduce the efficiency of the phytohormones used in a reduced way. The treatments T2, T3, T4 and T5 showed similar behavior in both harvests; however, treatments using ethephon (V and 15DAC) showed high variability of results in both harvests. It was observed that the application of etefom at a dose of 200 mg?L-1 at the time of color change caused early degeneration, sensitivity of the epidermis and rupture of berries still in the ripening stage, in both production cycles. The application of ABA at a concentration of 600 mg?L-1 induced higher levels of soluble solids in the berries. The wines produced with this treatment showed higher levels of ethanol and intense color. Wines produced with this same treatment also showed a reduction in the tonality and total acidity of musts and wines. Thus, the results obtained in this study showed that the application of ABA 15 days before harvest in the concentration of 600 mg?L-1 can be a management alternative to increase the levels of phenolic compounds and anthocyanins in wines and grape musts cv. Merlot, grown in the Serra Gaúcha. [resumo fornecido pelo autor]
A uva Merlot é uma cultivar de origem francesa, proveniente da Região de Bordeaux. Na Serra Gaúcha, é a segunda variedade tinta com maior área de vinhedo implantado, com 472 ha. Atualmente, a viticultura vem utilizando reguladores vegetais como alternativa para promover um incremento na qualidade dos mostos. O ácido abscísico e o etefom são alternativas utilizadas para suprir a falta de cor das bagas causada por adversidade climática em regiões com baixa amplitude térmica e períodos chuvosos ou nublados na fase de maturação. Este reguladores vegetais promovem acúmulo dos pigmentos que conferem coloração às bagas. Com o objetivo de verificar o efeito da aplicação de ácido abscísico (ABA) e etefom na qualidade final dos vinhos da cv. Merlot, o presente experimento foi executado em dois vinhedos comerciais, localizados nos municípios de Campestre da Serra, com coordenadas geográficas 28°40' S e 51°06' W, e Antônio Prado, com coordenadas geográficas 28°53' S 51°20' W, ambos localizados na Serra Gaúcha, Sul do Brasil. Os tratamentos foram aplicados em dois estágios: virada de cor (V) e 15 dias antes da colheita (15 DAC). Os seguintes tratamentos foram aplicados: T0 (testemunha); T1 (etefom 200 mg?L -1 - V); T2 (etefom (200 mg?L-1 - 15 DAC); T3 (etefom 200 mg?L-1 - V + S-ABA 600 mg?L-1 - 15 DAC); T4 (S-ABA 600 mg?L-1- V); T5 (S-ABA 600 mg?L-1- 15 DAC); T6 (S-ABA 300 mg?L-1 - V + S-ABA 300 mg?L-1 - 15 DAC); T7 (S-ABA 600 mg?L-1 - V + etefom 200 mg?L-1 - 15 DAC). Determinaram-se os seguintes parâmetros para as uvas: massa e diâmetro de bagas, teor de sólidos solúveis, pH do mosto, teor de compostos fenólicos e antocianinas. Para vinhos, foi avaliado o teor de álcool (etanol), coloração, densidade, acidez total, índice de cor e tonalidade. Os resultados mostraram que a localização dos vinhedos e o clima não influenciaram de forma significativa a eficiência dos fitormônios empregados. Os tratamentos T2, T3, T4 e T5 apresentaram comportamento semelhante em ambas às safras; no entanto, os tratamentos utilizando etefom (V e 15DAC) apresentaram variabilidade de resultados em ambas as safras. Observou-se que a aplicação de etefom na dose de 200 mg?L-1 no momento de virada de coloração causou desgrane precoce, sensibilidade da epiderme e ruptura de bagas ainda em fase de maturação, em ambos os ciclos produtivos. A aplicação de ABA na concentração de 600 mg?L-1 induziu maiores teores de sólidos solúveis nas bagas. Os vinhos produzidos com este tratamento apresentaram maiores teores de etanol e coloração mais intensa. Os vinhos produzidos com este mesmo tratamento também apresentaram redução da tonalidade e da acidez total dos mostos e vinhos. Desta forma, os resultados obtidos neste estudo mostraram que a aplicação de ABA 15 dias antes da colheita na concentração de 600 mg?L-1 pode ser uma alternativa de manejo para incrementar os teores de compostos fenólicos e antocianinas nos vinhos e mostos de uvas cv. Merlot, cultivadas na Serra Gaúcha. [resumo fornecido pelo autor]
Keywords: Vitivinicultura; Uva - Cultivo; Vinho tinto; Plantas; Viticulture; Grapes - Growing; Wine and wine making; Plants